AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY TOWARD THEIR SPEAKING SKILL - Juni Bayu Saputra (Premise: Journal of English Education and Applied Linguistics, 2018)
This article points out the results of the study attempting to analyze the students speaking anxiety at students in one of the College of Teacher Training and Education (STKIP) in Lampung. For the purpose of the topic, 28 fellow students were selected as the sample. Research method was quasi-experimental design with two way ANOVA. It was conducted for about four months. According to the results of speaking test, findings showed that using Communicative Language Teaching (CLT) had positive meaningful effect on improving students’ speaking skill viewed from different speaking anxiety. To sum up, CLT is an effective method to teach students’ speaking skill viewed from different speaking anxiety.